The impact of electronic games on the Jordanian Basic/ Secondary school students during the COVID- 19 Pandemic - Hind M Al-Braizat (Taez University, 2021)
This qualitative study aimed to investigate the direct impact of playing video games on Basic/ Secondary students during lockdown caused by COVID-19. A total number of 16 selected participants who were basic/secondary school students and one of each students' responsible parents were interviewed. Findings of the study suggest Corona Virus has contributed to the creation of an opportunity for students to play electronic games more than ordinary days until playing e-games became an addiction among some students, as it is the only means available to them to fill their free time during the lockdown and to get rid of their complaining and keep them busy as this negatively affects Students' interest, behaviors, and health. This study recommended that parents and leading experts should take initiatives (comprehensive programs, plans, and proper training) to support students get rid of addiction to video games during the lockdown and enable them to return to normal life and be prepared to attend schools once it is re-open.